The importance of competency for extensionists’ job performance in process of technology transfer - Tiraieyari, Neda; Idris, Khairuddin; Hamzah, Azimi; Uli, Jegak (Centre for Extension, Entrepreneurship and Professional Advancement (APEEC), Universiti Putra Malaysia, 2010)
This study sought to determine relationships between competencies and extensionists’ job performance in relation to the Good Agricultural Practices. Stratified random sampling technique employed to select 210 extensionists from the Department of Agriculture in four states of Malaysia. The quantitative data were analyzed using Pearson correlation analysis. Findings supported positive relationship between competencies and extensionists’ job performance. Job performance is positively related to social competency (r=.588, p=.001), Program planning competency (r=.586, p=.001), Program implementation competency (r=.528, p=.001), Program evaluation competency (r=.653, p=.001), Technical competency (r=.356, p=.001), Cultural competency (r=.611, p=.001), Extension teaching method competency (r=.582, p=.001), Leadership development competency (r=.472, p=.001) and Problem solving/decision making development competency (r=.507, p=.001). This study showed a high relationship between competencies and extensionists’ job performance in process of technology transfer.